2010
DOI: 10.1603/en09257
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an Aggregation Pheromone inHylesinus pruinosus(Coleoptera: Curculionidae: Scolytinae)

Abstract: We conducted laboratory and field bioassays to characterize the pheromone system of an ash bark beetle, Hylesinus pruinosus Eichhoff (Coleoptera: Curculionidae: Scolytinae). Solitary females in newly initiated galleries in ash logs produced (+)-exo-brevicomin, whereas male beetles paired with females produced (+)-endo-brevicomin, lesser quantities of (+)-exo-brevicomin, and a third compound that could not be identified. Beetles produced these compounds also after exposure to juvenile hormone III, and they were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Thus, it is not necessary for the compound to be released from an attractant-baited trap for D. frontalis catches to be enhanced. However, removal of the endo -brevicomin device from the trap greatly reduced catches of H. pruinosus and E. nigripes, suggesting that these species orient close to the source of endo -brevicomin which is for them an attractant rather than a synergist ( Shepherd et al 2010 ). Simultaneously, T. dubius does not show behavioral responses to endo -brevicomin ( Salom et al 1992 , Sullivan et al 2016 ), and therefore its placement is irrelevant to this species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is not necessary for the compound to be released from an attractant-baited trap for D. frontalis catches to be enhanced. However, removal of the endo -brevicomin device from the trap greatly reduced catches of H. pruinosus and E. nigripes, suggesting that these species orient close to the source of endo -brevicomin which is for them an attractant rather than a synergist ( Shepherd et al 2010 ). Simultaneously, T. dubius does not show behavioral responses to endo -brevicomin ( Salom et al 1992 , Sullivan et al 2016 ), and therefore its placement is irrelevant to this species.…”
Section: Discussionmentioning
confidence: 99%
“…A sympatric species of D. frontalis , the ash bark beetle, Hylesinus pruinosus Eichhoff (Coleoptera: Curculionidae: Scolytinae), employs (+)- endo -brevicomin as an aggregation pheromone component and is strongly attracted to lures with either racemic or (+)- endo -brevicomin ( Shepherd et al 2010 ). Similarly, the sympatric bark beetle predator Enoclerus nigripes (Say) (Coleoptera: Cleridae) is attracted to endo -brevicomin, presumably utilizing this compound as a host-location kairomone.…”
mentioning
confidence: 99%
“…The JHIII topical treatment was prepared by dissolving 10 mg of synthetic JHIII (CAS: 24198-95-6, SC-252931, Santa Cruz Biotechnology, 10410 Finnell Street, Dallas, TX 75220, US) in 250 µL of acetone (analytical reagent grade, Reanal, Budapest, Hungary) to make a 40 µg/µL stock solution. To treat female beetles, 0.5 µL of the solution containing 20 µg JHIII were administrated by a bevel-tip Hamilton syringe to the ventral abdominal surface of females, as described by Shepherd et al (2010). Beetles were incubated in a Petri-dish for one day under ambient conditions.…”
Section: Preparations Of Mid-and Hindgut Extractsmentioning
confidence: 99%
“…Earlier we showed that the calling sex of P. aubei is the female (Bozsik and Szőcs 2017), therefore we used females for pheromone extraction in this study. As it is well known that juvenile hormone III (JHIII) triggers pheromone production in many bark beetle species (Shepherd et al 2010;Chiu et al 2018), we prepared extracts of females pre-treated with JHIII and those without treatment (control).…”
Section: E)mentioning
confidence: 99%
“…For treatments, synthetic juvenile hormone III (10 mg, CAS: 24198-95-6, SC-252931, Santa Cruz Biotechnology, 10410 Finnell Street, Dallas, TX 75220, US) was dissolved in in 250 µL acetone (analytical reagent grade, Reanal, Budapest, Hungary). At treatment, 0.5 µL of the solution containing 20 µg JHIII were administrated by a bevel-tip Hamilton syringe to the ventral abdominal surface of females, as described by Shepherd et al (2010). Beetles were incubated in a Petri-dish for one day under ambient conditions.…”
Section: E)mentioning
confidence: 99%